2020
DOI: 10.3390/rs12010113
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Classification of Plants: A Review of Waveband Selection Generalisability

Abstract: Hyperspectral sensing, measuring reflectance over visible to shortwave infrared wavelengths, has enabled the classification and mapping of vegetation at a range of taxonomic scales, often down to the species level. Classification with hyperspectral measurements, acquired by narrow band spectroradiometers or imaging sensors, has generally required some form of spectral feature selection to reduce the dimensionality of the data to a level suitable for the construction of a classification model. Despite the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 82 publications
6
96
0
1
Order By: Relevance
“…Several studies reported the strong correlation between reflectance bands and yield in different crop plants such as alfalfa ( Kayad et al, 2016 ; Feng et al, 2020 ), wheat ( Prey and Schmidhalter, 2019 ), maize ( Lane et al, 2020 ), rice ( Wan et al, 2020 ), and sugarcane ( Verma et al, 2020 ). The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ). Most studies were emphasized the importance of red spectral bands or the combined use of red and red edge bands as one solid index in predicting the total yield ( Jolly et al, 2005 ; Filippa et al, 2018 ; Lykhovyd, 2020 ; Phan et al, 2020 ; Tiwari and Shukla, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the strong correlation between reflectance bands and yield in different crop plants such as alfalfa ( Kayad et al, 2016 ; Feng et al, 2020 ), wheat ( Prey and Schmidhalter, 2019 ), maize ( Lane et al, 2020 ), rice ( Wan et al, 2020 ), and sugarcane ( Verma et al, 2020 ). The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ). Most studies were emphasized the importance of red spectral bands or the combined use of red and red edge bands as one solid index in predicting the total yield ( Jolly et al, 2005 ; Filippa et al, 2018 ; Lykhovyd, 2020 ; Phan et al, 2020 ; Tiwari and Shukla, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gives a total of 204,800 combinations to work with, which should be enough to configure a training/testing dataset. Although this high dimensionality could offer potential problems to hyperspectral data processes [65], studies already suggested that maintaining the original data could also outperform feature-selected subsets [66,67]. It is also important to address that, although hyperspectral data is relatively easy to obtain, leaf tissue analysis can be limited.…”
Section: Machine Learning Analysis and Hyperspectral Mappingmentioning
confidence: 99%
“…As a discussion example, a recent paper collected 500 samples per class with 540 spectral bands and adopted a Cross-Validation method with a dataset considering 200 samples for each validation to demonstrate the importance of the feature selection methods [65]. Regardless, hyperspectral data have a characteristic distinct from most data, which is a high number of bands/wavelengths available to model a given problem.…”
Section: Machine Learning Analysis and Hyperspectral Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hennessy et al (2020) [57], in their review on the hyperspectral classification of plants, highlighted the importance of testing multiple feature selection and classification methods due to the high variation in outcomes among studies. Out study supports this statement.…”
Section: Automated Species Identification Using Hyperspectral Datamentioning
confidence: 99%